PENINGKATAN KUAT TARIK BETON AKIBAT PENAMBAHAN SERAT SABUT KELAPA - Elhusna Elhusna; Jefri Suwandi (Universitas Bengkulu, 2019)
Five variations of fibre coconut were used to find out the ability of the fibre to enhance the concrete tensile strength. The coconut fibre (1%, 2%, 3%, 4% and 5% of the volume of the specimen) was added during mixing the concrete. the mix design of the concrete was done at 0,5 water cement ratio and 30-60 mm of slump value. SNI 03-2493-2002 was the standar that used for casting and curing the silinder (diameter/height;150/300 mm) while the split cylinder test was done according to SNI 03-2491-2002. The results showed that the addition of coconut fibre was significantly enhance the tensile strength of the fibre concrete. The correlation between the fibre and the tensile strength was given in quadratic equation which the correlation coeficient ( R2 ) was 0,982. The addition of 5% of the fibre enhanced the tensile strength up to 64,66% of the fibre concrete compared to the concrete without the fibre.